A modern approach to the preschool education system.: A modern approach to the preschool education system. - G'aniyeva, Hayriniso; Umurzoqova, Aziza (Maktabgacha taʼlim jurnali, 2022)
The economic power of each country, the rise in the level of social and spiritual life is determined by the competitiveness of the educational system and the development of science.